Radio-Frequency Identification (RFID) Item Finder Using Radio Frequency Energy Harvesting - Indra, Win Adiyansyah; Wong, Adam Yoon Khang; Yap, Thai Yung; Jamil Alsayaydeh, Jamil Abedalrahim (Asian Research Publishing Network, 2019)
This paper investigates Radio Frequency Identification (RFID) finder powered by Radio Frequency Energy Harvesting. Misplaced and losing item is a normal situation that happens almost anytime and anywhere. When this problem occurs in situation during the emergency time or in hurry, panic will come and start searching around for that lost item from where it was last seen it or place it. RFID is a technology that is used for item identification. A RFID Item Finder is developed with the Radio Frequency (RF) Energy Harvesting technology. The Output of RF Energy Harvesting is used as the input source for the RFID Item Finder by converting RF signal source to DC source that needed by the Item Finder. A RFID tag is attached over the item so that it can be searched by using RFID reader which if the tag in a read zone of the reader, user can know whether the misplaced item is in that certain area by the communication between RFID tag and reader.